2011
DOI: 10.1111/j.1365-2796.2011.02375.x
|View full text |Cite
|
Sign up to set email alerts
|

Shared genetics in coeliac disease and other immune-mediated diseases

Abstract: Abstract. Gutierrez-Achury J, Coutinho de Almeida R,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 96 publications
0
53
0
3
Order By: Relevance
“…Importantly, this study also demonstrated that nearly 50% of CD risk SNPs are in close proximity to expression quantitative trait loci (eQTLs), suggesting a likely role for changes in levels of gene expression in CD. As mentioned above, additional GWA studies have identified risk loci shared between CD and other autoimmune conditions such as T1DM, RA, CrD, and ulcerative colitis (UC) (Zhernakova et al 2007(Zhernakova et al , 2011Smyth et al 2008;Barrett et al 2009;Festen et al 2009Festen et al , 2011Cotsapas et al 2011;Gutierrez-Achury et al 2011). These studies have illuminated the tremendously pleiotropic nature of loci underlying autoimmune and other immune related conditions.…”
Section: Presentation Pathophysiology and Genetics Of CDmentioning
confidence: 99%
“…Importantly, this study also demonstrated that nearly 50% of CD risk SNPs are in close proximity to expression quantitative trait loci (eQTLs), suggesting a likely role for changes in levels of gene expression in CD. As mentioned above, additional GWA studies have identified risk loci shared between CD and other autoimmune conditions such as T1DM, RA, CrD, and ulcerative colitis (UC) (Zhernakova et al 2007(Zhernakova et al , 2011Smyth et al 2008;Barrett et al 2009;Festen et al 2009Festen et al , 2011Cotsapas et al 2011;Gutierrez-Achury et al 2011). These studies have illuminated the tremendously pleiotropic nature of loci underlying autoimmune and other immune related conditions.…”
Section: Presentation Pathophysiology and Genetics Of CDmentioning
confidence: 99%
“…In Europe and the United States, the prevalence varies between 1 and 3% in the general population (4). The prevalence of CD confirmed by biopsy, in studies performed in Brazil to date, show a variation of 0.15 to 1.94% (5).…”
Section: Introductionmentioning
confidence: 99%
“…For example although autoimmune diseases often affect specific organs, they might also have more systematic manifestations [42]. Examples include coeliac disease which primarily damages intestinal mucosa, but may also have neurological, psychiatric, or thyroid manifestations [42]. Moreover in [42] authors claim that most if not all of dysregulated processes involved in autoimmune diseases will in fact at some point result in T-cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include coeliac disease which primarily damages intestinal mucosa, but may also have neurological, psychiatric, or thyroid manifestations [42]. Moreover in [42] authors claim that most if not all of dysregulated processes involved in autoimmune diseases will in fact at some point result in T-cell activation. Indeed, T cells are, either primarily or secondarily, involved in allergic, autoimmune, infectious, and malignant diseases [43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation